Dirofilaria in Humans, Dogs, and Vectors in Austria (1978-2014)-From Imported Pathogens to the Endemicity of Dirofilaria repens. - Hans-Peter Fuehrer; Herbert Auer; Michael Leschnik; Katja Silbermayr; Georg Duscher; Anja Joachim (Public Library of Science (PLoS), 2016)
BACKGROUND:Dirofilaria repens and D. immitis are filarioid helminths with domestic and wild canids as main hosts and mosquitoes as vectors. Both species are known to cause zoonotic diseases, primarily pulmonary (D. immitis), ocular (D. repens), and subcutaneous (D. repens) dirofilariosis. Both D. immitis and D. repens are known as invasive species, and their distribution seems associated with climate change. Until very recently, both species were known to be nonendemic in Austria. METHODOLOGY AND PRINCIPAL FINDINGS:Metadata on introduced and possibly autochthonous cases of infection with Dirofilaria sp. in dogs and humans in Austria are analysed, together with analyses of mosquito populations from Austria in ongoing studies. In Austria, most cases of Dirofilaria sp. in humans (30 cases of D. repens-six ocular and 24 subcutaneous) and dogs (approximately 50 cases-both D. immitis and D. repens) were most likely imported. However, occasionally infections with D. repens were discussed to be autochthonous (one human case and seven in dogs). The introduction of D. repens to Austria was confirmed very recently, as the parasite was detected in Burgenland (eastern Austria) for the first time in mosquito vectors during a surveillance program. For D. immitis, this could not be confirmed yet, but data from Germany suggest that the successful establishment of this nematode species in Austria is a credible scenario for the near future. CONCLUSIONS:The first findings of D. repens in mosquito vectors indicate that D. repens presumably invaded in eastern Austria. Climate analyses from central Europe indicate that D. immitis also has the capacity to establish itself in the lowland regions of Austria, given that both canid and culicid hosts are present.